Immobilization of manganese dioxide nanoparticles on modified poly 2, 4-dichlorostyrene microspheres: a highly efficient and recyclable catalyst for borrowing hydrogen reactions. Issue 19 (9th September 2019) - Qiu, Ye; Zhang, Yilin; Jin, Lu; Pan, Le; Du, Guangming; Ye, Dongdong; Wang, Dawei
Abstract : Modified poly 2, 4-dichlorostyrene microspheres were designed and synthesized, and were proved to be an effective carrier to synthesize supported manganese dioxide nanoparticles. Abstract : Manganese dioxide nanoparticles have been fabricated using a facile approach and immobilized onto the surface of modified poly 2, 4-dichlorostyrene microspheres. The resulting multifunctional hybrid materials were characterized by scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray power diffraction and X-ray photoelectron spectrometry. This cheap heterogeneous manganese catalyst revealed excellent reactivity and stability for the direct alkylation of primary alcohols with ketones via a hydrogen borrowing pathway. In addition, this catalytic system could be readily recycled more than five times with high reactivity retained, which provided a practical atom-economical approach for C–C bond formation and 1-benzyl-2-aryl-1 H -benzo[ d ]imidazole synthesis. Mechanism investigations were conducted to better understand this catalyst system and these transformations.